Analyzing the impact of population size, regional minimum wage, and economic growth on unemployment - Sepdianty, Ika; Tuah, Sunaryo N (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
The problem of unemployment is indeed very complex to discuss, because it can be related to several economic indicators that have a relationship with the open unemployment rate. The role of the government is needed to overcome the problem of unemployment in the region. Uncontrolled population numbers can result in not achieving economic development goals. The success of economic development can be seen from economic growth and the smaller inequality in an area, with the increasing economic development of a region, it is expected to be able to reduce the existing unemployment rate where welfare will be achieved properly. This study has a purpose: to analyze the effect of population, regional minimum wages, and economic growth on the open unemployment rate in Central Kalimantan. This study uses secondary data which is time series data from 2013-2019. Analysis of the data used is panel data with the help of the eviews program. The result of this study is that the variables of population, regional minimum wage, and economic growth have a positive effect on the open unemployment rate in Central Kalimantan. When the population increases and when real wages increase, companies will reduce the demand for labor, while the supply of labor is higher than the demand for labor, then this causes the unemployment rate to increase